High‐Temperature Stability Amorphous Ternary AlBN Dielectric Films on N++GaN. Issue 10 (2nd May 2022) - Liu, Fengfeng; Li, Yuxiong; Devaux, Xavier; Lu, Yuan; Luo, Yi; Sui, Zhanpeng; Cai, Yong; Jiang, Chunping
Abstract : Dielectric films have played a vital role in the development of micro‐ and nanoelectronic devices over the past decades. However, the stability of current dielectrics under extreme high‐temperature conditions is still a major shortcoming to be overcome. Herein, the successful fabrication of high‐quality amorphous ternary AlBN dielectric films on n ++ GaN substrates by pulsed laser deposition (PLD) at room temperature (25 ± 2 °C) is reported. Systematic characterizations on the morphology, structure, chemical composition, and band offsets properties of the fabricated films reveal that both as‐deposited and 800 °C postdeposition annealing (PDA) thin films are amorphous and exhibit good physical and electrical properties. Large band offsets (>2.0 eV), high dielectric constants (>10), and low leakage currents are achieved in both cases. Furthermore, the leakage current density in the Au/AlBN/n ++ GaN junctions of 800 °C PDA thin films is reduced by approximately one order of magnitude compared with those of as‐deposited thin films. The demonstration of these excellent properties indicates that the amorphous AlBN dielectric thin films are promising candidates for integrated dielectric layers in electronic devices for harsh environment applications. Abstract : The realization of high‐temperature stable amorphous dielectric films is important for high current density, breakdown field, frequency, and temperature performance in III‐nitride semiconductor devices. Herein, by introducing boron (B) atoms into the amorphous AlN film, both as‐deposited and 800 °C postdeposition annealing (PDA) ternary AlBN dielectric films are amorphous and exhibit good physical and electrical properties.